STUDY HABITS AND TEST ANXIETY OF HIGHER SECONDARY SCHOOL STUDENTS IN MALAPPURAM DISTRICT - Anne Mary Thomas and V. J. Joseena (Conflux Journal of Education, 2013)
Academic success has been investigated extensively and several factors have emerged as critical in academic success. This paper discusses about the Study Habits and Test Anxiety of HigherSecondary School Students in Malappuram District. The sample consists of Four Hundred Higher Secondary School Students with Science and Humanities as their Subjects under study. The tools used were Study Habits Inventory and Test Anxiety Scale for Higher Secondary Students; both are constructed and standardized by the investigators. The analysis of data using appropriate statistical techniques revealed that there exist a significant positive correlation between Study Habits and Test Anxietyof Higher Secondary School Students in Malappuram District.